Raton Museum (Raton, NM Raton Range, 1977)
This article is announcing Tom Burch as the Curator of the Raton Historical Museum.
Newspaper article
Master list item #: 82
File location is in the Raton file Cabinet
Keywords: Burch, Thomas (Tom) -- Curator; Rubin, Karen -- Museum Board vice-president; Ritchey, Carl; Raton Historical Museum; New Curator; Board Changes; Museum Business; Raton, New Mexico